2019
DOI: 10.1101/cshperspect.a036400
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Regulation of Gasdermin-Mediated Cell Death

Abstract: The innate immune system senses and responds to pathogens and endogenous damage through supramolecular protein complexes known as inflammasomes. Cytosolic inflammasome sensor proteins trigger inflammasome assembly on detection of infection and danger. Assembled inflammasomes activate a cascade of inflammatory caspases, which process procytokines and gasdermin D (GSDMD). Cleaved GSDMD forms membrane pores that lead to cytokine release and/or programmed lytic cell death, called pyroptosis. In this review, we pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
88
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(90 citation statements)
references
References 86 publications
(134 reference statements)
1
88
0
1
Order By: Relevance
“…GSDME has been proposed as a tumor suppressor, and is now believed to be a strategy to boost the immunogenicity of cancer cell death. 30,31 Our results demonstrated that GSDME knockdown prevented secondary necrosis and fibrogenesis in diabetic tubular cells. Our work brings about an advance in identifying GSDME as a promising target for the treatment of DKD.…”
Section: Discussionmentioning
confidence: 57%
“…GSDME has been proposed as a tumor suppressor, and is now believed to be a strategy to boost the immunogenicity of cancer cell death. 30,31 Our results demonstrated that GSDME knockdown prevented secondary necrosis and fibrogenesis in diabetic tubular cells. Our work brings about an advance in identifying GSDME as a promising target for the treatment of DKD.…”
Section: Discussionmentioning
confidence: 57%
“…This process is thought to promote the extracellular release of nuclear HMGB1 during infections (Lamkanfi et al, 2010). While the secretion of lactate dehydrogenase (LDH), HMGB1, and IL-1β occurs without rupture, HMGB1 can be released to the extracellular matrix via passive diffusion through Gasdermin D pores (Davis et al, 2019;Miao et al, 2019), and living cells are capable of releasing inflammasome related cytokines via the Gasdermin D pore without the development of pyroptosis (Xia et al, 2019). Another novel finding is that GPX4 deficiency increases lipid peroxidation, thus exacerbating GSDMD-mediated pyroptosis in macrophages as well as septic lethality in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of caspase-11 non-canonical inflammasome induces the proteolytic activation of gasdermin D (GSDMD) at the 276 aspartic acid residue to produce the N-terminal pore-forming domain and the C-terminal autoinhibitory domain of GSDMD. The N-terminal pore-forming domain of GSDMD (N-GSDMD) moves to the cell membrane to generate N-GSDMD-mediated large barrel-shaped transmembrane pores that are 27-fold symmetric oligomers [13]. The N-GSDMD pores are 18 nm in inner diameter and allow the secretion of a number of cytoplasmic molecules to the extracellular space including pro-inflammatory cytokines, IL-1β and IL-18.…”
Section: Caspase-11 Non-canonical Inflammasome-activated Inflammatorymentioning
confidence: 99%
“…The N-GSDMD pores are 18 nm in inner diameter and allow the secretion of a number of cytoplasmic molecules to the extracellular space including pro-inflammatory cytokines, IL-1β and IL-18. N-GSDMD pores also increase in osmotic pressure, leading to an influx of extracellular water followed by cell swelling, and eventually to cell lysis known as pyroptosis, an inflammatory form of apoptosis [12][13][14]37]. Pyroptosis is a part of the anti-microbial inflammatory response.…”
Section: Caspase-11 Non-canonical Inflammasome-activated Inflammatorymentioning
confidence: 99%